Association of corneal endothelial cell morphology with neurodegeneration in mild cognitive impairment and dementia - Georgios Ponirakis; Hanadi Al Hamad; Alaa S. Al‐Waisy; Ioannis N. Petropoulos; Adnan Khan; Hoda Gad; Mani Chandran; Masharig Gadelseed; Salah Mahmoud; Ahmed Elsotouhy; Marwan Ramadan; Shafi Khan; et al. (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract INTRODUCTION Corneal confocal microscopy (CCM) detects neurodegeneration in mild cognitive impairment (MCI) and dementia and identifies subjects with MCI who develop dementia. This study assessed whether abnormalities in corneal endothelial cell (CEC) morphology are related to corneal nerve morphology, brain volumetry, cerebral ischemia, and cognitive impairment in MCI and dementia. METHODS Participants with no cognitive impairment (NCI), MCI, and dementia underwent CCM to quantify corneal endothelial cell density (CECD) and area (CECA), corneal nerve fiber morphology, magnetic resonance imaging (MRI) brain volumetry, and severity of brain ischemia. RESULTS Of the 114 participants, 14 had NCI, 77 had MCI, and 23 had dementia. CECD (1971.3 ± 594.6 vs 2316.1 ± 499.5 cells/mm2, p < 0.05) was significantly lower in the dementia compared to the NCI group. CECD and CECA were comparable between the MCI and NCI groups (p = 0.13–0.65). Corneal nerve fiber density (CNFD) (31.7 ± 5.6 vs 24.5 ± 9.2 and 17.3 ± 5.3 fibers/mm2, p < 0.01), corneal nerve branch density (CNBD) (111.8 ± 58.1 vs 50.4 ± 36.4 and 52.7 ± 21.3 branches/mm2, p < 0.0001), and corneal nerve fiber length (CNFL) (24.6 ± 6.6 vs 16.5 ± 6.8 and 16.2 ± 5.0 mm/mm2, p < 0.0001) were lower in the MCI and dementia groups compared to the NCI group. Lower CECD partially mediated the impact of age and diabetes on CNFL reduction (p < 0.05), whereas CECA lost its significance after adjustment (p = 0.20). CEC morphology does not affect the association between corneal nerve fiber loss and MCI/dementia. CECD and CECA had no significant association with cerebral ischemic lesions (p = 0.21–0.47), dementia (p = 0.11–0.35), or cognitive decline (p = 0.37–0.38). However, lower CECD and higher CECA were associated with decreased cortical gray matter volume (p < 0.05–0.01). DISCUSSION CEC loss occurs in patients with dementia, and both endothelial cell loss and hypertrophy are associated with cortical gray matter atrophy. CNF loss occurs in individuals with MCI and dementia. Corneal nerve and endothelial cell abnormalities could act as biomarkers for neurovascular pathology in dementia. Highlights Corneal endothelial cell density is significantly reduced in patients with dementia. Corneal nerve fiber density, branch density, and length are lower in subjects with mild cognitive impairment (MCI) and dementia. Corneal endothelial cell loss and hypertrophy are associated with cortical gray matter atrophy. Corneal nerve and endothelial cell abnormalities could act as biomarkers for neurovascular pathology in dementia. Reduced corneal endothelial cell density partially mediates the effects of age and diabetes on corneal nerve fiber loss.